Comprehensive structural analysis of the open and closed conformations of Theileria annulata enolase by molecular modelling and docking - MUTLU, ÖZAL; DANIŞ, ÖZKAN (ELSEVIER SCI LTD, 2016)
Theileria annulata is an apicomplexan parasite which is responsible for tropical theileriosis in cattle. Due to resistance of T. annulata against commonly used antitheilerial drug, new drug candidates should be identified urgently. Enolase might be a druggable protein candidate which has an important role in glycolysis, and could also be related to several cellular functions as a moonlight protein. In this study; we have described three-dimensional models of open and closed conformations of T. annulata enolase by homology modeling method for the first time with the comprehensive domain, active site and docking analyses. Our results show that the enolase has similar folding patterns within enolase superfamily with conserved catalytic loops and active site residues. We have described specific insertions, possible plasminogen binding sites, electrostatic potential surfaces and positively charged pockets as druggable regions in T. annulate enolase. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Enolase; Homology modeling; Molecular docking; TRYPANOSOMA-BRUCEI ENOLASE; CRYSTAL-STRUCTURE; HIGH-ACCURACY; ACTIVE-SITE; GENE; ELECTROSTATICS; IDENTIFICATION; VISUALIZATION; PLASMINOGEN; SUPERFAMILY